The Tipping Point in Psychopathy: Role of Psychopathic Traits in Trauma Exposure - Gupta, Sneha M (2020)
Though psychopathy has been associated with a socially deviant lifestyle, the idea of “successful” psychopathy has gained increased attention. Previous research has explored whether psychopathic traits play a role in trauma exposure/ PTSD, using clinical and forensic populations. Results from these studies suggest that Factor 1 traits may protect from trauma exposure (Factor 1 Theory) while Factor 2 traits may worsen the impact of trauma through exacerbated exposure to traumatic events. The objective of this study was to explore the relationship between each of Factor 1 traits and Factor 2 traits with trauma exposure and PTSD. In a sample of 86 emergency responders and 104 community members, Factor 1 did not show a significant association with trauma exposure (community or emergency responder samples) but showed a negative and significant association with PTSD (community and emergency responders samples); Factor 2 showed a significant positive association with trauma exposure (community sample) and PTSD (community and emergency responders samples). Factor 1 had a significant moderation effect on the relationship between trauma exposure and PTSD (community sample) suggesting a protective effect. Factor 2 did not have a significant moderating effect in any of the samples. This study used a population that has not been studied before (emergency responders) in the context of psychopathy and trauma. By furthering research on this topic, appropriate intervention methods can be developed to assist such sub-groups that are faced with high trauma exposure on a daily basis. (238 words) Keywords: psychopathy; trauma; PTSD; TriPM; emergency responders; life events checklist, PTSD checklis